PP52 Obesity Prevention in Scotland: A Policy Analysis using the Angelo Framework. (10th September 2013) - Mooney, J D; Frank, J; Jepson, R; Geddes, R
Abstract : Background: The Scottish Government's 'Route-Map towards Healthy Weight' published in 2010, aspired towards a comprehensive cross-government approach to tackling the rising prevalence of obesity, with commitments to addressing the fundamental societal drivers of the epidemic. The subsequent 'Route-Map Action Plan' set out 62 policies targeted at nutrition, physical activity or both, at all stages of the life course. We categorised each policy using the ANGELO Framework (Analysis Grid for Environments Linked to Obesity), to assess the appropriateness and likely impact of the balance of measures being proposed. ANGELO uses four broad 'domains': Physical, Economic, Legislative and Socio-cultural, as well as two 'scales' of intervention: 'Macro' for the national, regional or sectorial level and 'Micro' for the local neighbourhood/community/institutional level. Methods: Two assessors (JM & RJ), used the guidance outlined by the originators of ANGELO to independently allocate a category for each intervention according to its domain (Physical, Economic, Legislative or Socio-cultural), scale (Macro or micro); and predominant 'focus' (activity versus nutrition). A third assessor (RG) then examined those policies where there were differences in allocation and a consensus on each was agreed by discussion. The resulting distribution of policies by scale and domain was compared with the current consensus of international research evidence around which combinations of measures are likely to have the greatest impact at a population level. Results: Across the four environmental domains, the distribution of the 62 separate policy initiatives was skewed towards behavioural (Socio-cultural) measures (37.1%) and the Physical environment (33.1%) (i.e. surroundings), with less emphasis on Legislative measures (21.8%) or Economic interventions (6.4%). The distribution of both intervention scale and focus was more evenly spread with just over half of all policies (51.8%) targeted at the Macro-level scale and just under half (46.7%) having a nutrition focus. Conclusion: Policy interventions (planned or underway), to tackle obesity which are supported by the Scottish Government, span across all four domains of the obesogenic environment as described by the ANGELO framework. The predominance of Socio-cultural/(i.e. behavioural) orientated interventions over Legislative and particularly Economic (or fiscal) measures (such as a sugared beverage tax), is common for most Governments, although the balance of evidence suggests that targeting the latter domains would be more effective. There is a need therefore to strive for a more balanced approach across all spheres of Government influence, with economic interventions representing the area where actions should particularly be increased.